In Situ Structures of Polar and Lateral Flagella Revealed by Cryo-Electron Tomography - Zhu, Shiwei (J Bacteriol, 2019)
The bacterial flagellum is a sophisticated self-assembling nanomachine responsible for motility in many bacterial pathogens, including Pseudomonas aeruginosa, Vibrio spp., and Salmonella enterica. The bacterial flagellum has been studied extensively in the model systems Escherichia coli and Salmonella enterica serovar Typhimurium, yet the range of variation in flagellar structure and assembly remains incompletely understood. Here, we used cryo-electron tomography and subtomogram averaging to determine in situ structures of polar flagella in P. aeruginosa and peritrichous flagella in S. Typhimurium, revealing notable differences between these two flagellar systems. Furthermore, we observed flagellar outer membrane complexes as well as many incomplete flagellar subassemblies, which provide additional insight into mechanisms underlying flagellar assembly and loss in both P. aeruginosa and S. Typhimurium. IMPORTANCE The bacterial flagellum has evolved as one of the most sophisticated self-assembled molecular machines, which confers locomotion and is often associated with virulence of bacterial pathogens. Variation in species-specific features of the flagellum, as well as in flagellar number and placement, results in structurally distinct flagella that appear to be adapted to the specific environments that bacteria encounter. Here, we used cutting-edge imaging techniques to determine high-resolution in situ structures of polar flagella in Pseudomonas aeruginosa and peritrichous flagella in Salmonella enterica serovar Typhimurium, demonstrating substantial variation between flagella in these organisms. Importantly, we observed novel flagellar subassemblies and provided additional insight into the structural basis of flagellar assembly and loss in both P. aeruginosa and S. Typhimurium.